Simplified Microneutralization Test for Serotyping Adenovirus Isolates - Malasig, Marietta D. (American Society for Microbiology, 2001)
A simplified microneutralization procedure is described that uses an empirically determined virus challenge dose, a single dilution of antiserum, and observation of cytopathic effect to determine the adenovirus serotype. The simplified test has faster turnaround time and was 96% concordant with a confirmatory test using serial dilutions of type-specific sera. This method will find utility in high-volume serotyping work.